The influence of social networks on young consumer (ADMPG Journal, 2025)
The differences in the personality traits of the generations caused by the context in which each one of them lived resulted, over time, in different types of buying behaviors. In this way, it is extremely important that companies understand the new consumption pattern of today's society and, based on that, work on possible future consumer trends. In view of this, the present work aims to analyze the characteristics of the young consumer and identify, through a quantitative survey, which social network has the greatest purchasing power over generation Z, thus analyzing the power of influence of digital marketing on social networks on this generation. From the results, it was possible to perceive the extreme importance that young people give to social networks, with the social network Instagram being the one that has the greatest influence on them. Because of this, companies currently need to be active on social networks, especially on Instagram, because it is in them that it is currently possible to produce marketing with greater reach, therefore, a greater chance of success.